Gene expression of cell surface antigens in the early phase of murine influenza pneumonia determined by a cDNA expression array technique - Shinya Sakai; Naoki Mantani; Toshiaki Kogure; Hiroshi Ochiai; Yutaka Shimada; Katsutoshi Terasawa (Hindawi Limited, 2002)
Background: Influenza virus is a worldwide health problem with significant economic consequences. To study the gene expression pattern induced by influenza virus infection, it is useful to reveal the pathogenesis of influenza virus infection; but this has not been well examined, especially in vivo study.